The last shall be first: Innovation as a head-to-head race - Patrick Arnold; Marc Möller; Catherine Roux (University of Bern, Department of Economics, 2025)
Uncertainty about the value of a contested innovation induces leaders and laggards to update their expectations in opposite directions. We characterize situations in which firms that have obtained an initial advantage are not the most likely to achieve final success. In spite of amplifying a leader's advantage, greater contest intensity facilitates this effect, challenging the view that laggards require support to remain competitive.
Keywords: C72; D82; 330; Innovation contests; learning; competitive balance; leapfrogging